ANALISIS KESULITAN MENDENGAR PADA SISWA KELAS IX SMP DARUDDA’WAH - Rahmadi, Nizar; Rian, Rian; Ismu Purwaningsih, Dewi; Yolanda, Alvina (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This study aims to explore the difficulties faced by students in understanding English dialogue and the factors that influence it. In the context of language learning, listening skills have a crucial role because they affect students' ability to speak and interact. Qualitative descriptive methods are used to explain these phenomena, by collecting data through questionnaires to analyze students' answers. The results of the study showed that 84.3% of students experienced major difficulties in identifying the content of the message. Lack of vocabulary mastery, inability to guess words in the recording, and the length of the message conveyed are the main factors. In addition, 71.8% of students had difficulties with speakers. Some of the problems encountered include the inability to listen without pictures or videos, the speaker's speaking speed being too high, and the variety of accents in the recording. From these results, it can be concluded that good listening skills are an important foundation in language learning. Therefore, there is a need for a learning strategy that is more focused on vocabulary development and understanding of various accents in the context of dialogue. This can help improve students' knowledge and respond to English conversations more effectively. The conclusion can be the basis for developing a more effective learning program in improving students' listening skills.